Menyelisik Posisi Anak dan Relasinya dengan Allah di Dalam Alkitab - Rolland Alexander Samson (Peneliti.net, 2020)
Bible is a fundamental base for Christian practice. It is important to see the theological reasons for Christians practice to one another. This article will be focused on the position of children in the bible and their relation with God as their Creator and its contribution to Christian behavior toward the children in the church and the society. Departed from studying the etymology of the terms applied for children in the bible, the literature research also guides this article to present the result that the children are mentioned very often in the bible in vary contexts and meanings. It displays also that God has extremely good relationship with children which is a recommendation for the Christians to have the good treats also to the children all over the world.